SOME MORPHOLOGICAL AND ECOLOGICAL FEATURES OF MAY CHA (Pseudosasa amabilis) IN DIEN BIEN PROVINCE - Xuan Truong, Le (Journal of Forestry Science and Technology, 2017)
The study was conducted in Muong Phang, Pa Khoang communes, Dien Bien district and Pu Nhi commune, Dien Bien Dong district, Dien Bien province. Four 500 m2 (20 m x 25 m) plots were set up in three communes that have May cha naturally distributed in secondary rehabilitation forest and plantation. May cha is Pseudosasa amabilis or Pseudosasa amabilis (McClure) Keng f.ex S.L.Chen & et al. It belongs to Pseudosasa genus, Arundinarieae tribus, Bambusoideae subfamilia, Poaceae familia, Poales order. It is a mixpodial bamboo. May cha in four plots had various growth indicators such as D00, Height, and morphological features and were much lower than that in the past. It showed that May cha in the survey area were degraded. In the survey areas May cha grew in IIIA1 secondary rehabilitation forest and Acacia plantation with natural regeneration that had crown closure from 0.3 to 0.8. The soil depth were from 70 to 92 cm, A and AB horizon were from 26 to 55 cm. Soil colors were black brown- yellow, black brown- red yellow, and black brown- red brown. Soil were relative moisture to moisture that had silt texture, granular structure, and porous to compaction. In the depth of 40cm (distribute horizon of May cha’s rhizome, stump, and root) soils had bulk density from 1.01 to 1.20; particle density from 2.52 to 2.74; porosity from 53.12 to 60.72%; humus content from 3.01 to 4.00%; Labile NH4+ from 1.56 to 2.09 mg/100gr soil; Labile P2O5 from 0.08 to 0.13 mg/100gr soil; Labile K2O from 2.62 to 3.93 mg/100gr soil; pHKCl from 5.6 to 5.9; and pHH2O from 6.0 to 6.2.